Improving cancer immunotherapy in prostate cancer by modulating T cell function through targeting the galectin-1 - Wang, Hsiao-Chi; Xia, Roger; Chang, Wen-Hsin; Hsu, Ssu-Wei; Wu, Chun-Te; Chen, Ching-Hsien; Shih, Tsung-Chieh (Frontiers in Immunology, 2024)
Our study aimed to elucidate the role of Galectin-1 (Gal-1) role in the immunosuppressive tumor microenvironment (TME) of prostate cancer (PCa). Our previous findings demonstrated a correlation between elevated Gal-1 expression and advanced PCa stages. In this study, we also observed that Gal-1 is expressed around the tumor stroma and its expression level is associated with PCa progression. We identified that Gal-1 could be secreted by PCa cells, and secreted Gal-1 has the potential to induce T cell apoptosis. Gal-1 knockdown or inhibition of Gal-1 function by LLS30 suppresses T cell apoptosis resulting in increased intratumoral T cell infiltration. Importantly, LLS30 treatment significantly improved the antitumor efficacy of anti-PD-1 in vivo. Mechanistically, LLS30 binds to the carbohydrate recognition domain (CRD) of Gal-1, disrupting its binding to CD45 leading to the suppression of T cell apoptosis. In addition, RNA-seq analysis revealed a novel mechanism of action for LLS30, linking its tumor-intrinsic oncogenic effects to anti-tumor immunity. These findings suggested that tumor-derived Gal-1 contributes to the immunosuppressive TME in PCa by inducing apoptosis in effector T cells. Targeting Gal-1 with LLS30 may offer a strategy to enhance anti-tumor immunity and improve immunotherapy.